A randomized, open‐label, active comparator trial assessing the effects of 26 weeks of liraglutide or sitagliptin on cardiovascular function in young obese adults with type 2 diabetes. Issue 7 (1st April 2020) - Webb, David R.; Htike, Zin Zin; Swarbrick, Daniel J.; Brady, Emer M.; Gray, Laura J.; Biglands, John; Gulsin, Gaurav S.; Henson, Joseph; Khunti, Kamlesh; McCann, Gerry P.; Waller, Helen L.; Webb, M'Balu A.; et al.
Abstract: Aim: To compare the effects of a glucagon‐like peptide‐1 receptor agonist and a dipeptidyl peptidase‐4 inhibitor on magnetic resonance imaging‐derived measures of cardiovascular function. Materials and methods: In a prospective, randomized, open‐label, blinded endpoint trial liraglutide (1.8 mg) and sitagliptin (100 mg) were compared in asymptomatic, non‐insulin treated young (aged 18‐50 years) adults with obesity and type 2 diabetes. The primary outcome was difference in circumferential peak early diastolic strain rate change (PEDSR), a biomarker of cardiac diastolic dysfunction 26 weeks after randomization. Secondary outcomes included other indices of cardiac structure and function, HbA1c and body weight. Results: Seventy‐six participants were randomized (54% female, mean ± SD age 44 ± 6 years, diabetes duration 4.4 years, body mass index 35.3 ± 6.1 kg m −2 ), of whom 65% had ≥1 cardiovascular risk factor. Sixty‐one participants had primary outcome data available. There were no statistically significant between‐group differences (intention‐to‐treat; mean [95% confidence interval]) in PEDSR change (−0.01 [−0.07, +0.06] s −1 ), left ventricular ejection fraction (−1.98 [−4.90, +0.94]%), left ventricular mass (+1.14 [−5.23, +7.50] g) or aortic distensibility (−0.35 [−0.98, +0.28] mmHg −1  × 10 −3 ) after 26 weeks. Reductions in HbA1c (−4.57 [−9.10, −0.37] mmol mol −1 ) and body weight (−3.88 [−5.74, −2.01] kg) were greater with liraglutide. Conclusion: There were no differences in cardiovascular structure or function after short‐term use of liraglutide and sitagliptin in younger adults with obesity and type 2 diabetes. Longer studies in patients with more severe cardiac dysfunction may be necessary before definitive conclusions can be made about putative pleiotropic properties of incretin‐based therapies.